Kawruh and Rahsa: Epistemic Relations of Indigenous Psychology With Javanese Traditions - Rochman, Kholil Lur; Faishol, Lutfi (Jurusan Bimbingan dan Konseling Islam, 2024)
Javanese culture is a treasure rich in symbols. That symbol is perceived and positioned by Javanese people as the basis of behavior and spirituality. Not only limited to rituals, Javanese traditions, especially kawruh and rahsa, also become a distinctive knowledge entity. It was from there that epistemic attempts were made to relate it to cultural psychology. In that regard, the purpose of this study is to discuss and explain these epistemic relationships in the indijnius psychological reason. This type of research is qualitative. This research data was obtained using a literature study. The library is used to find and comb through various research results that discuss Javanese culture in general and the concept of independent psychology. Data analysis was carried out critically to reveal the epistemic relationship between the concepts of kawruh and rahsa in the indijinius psychological reason. The results of this study show that psychological reason built on the behavior of Javanese people becomes a symbol or marker for the quality of personality of the community. The concept of kawruh and rahsa is a spirit in Javanese tradition that is able to elaborate epistemically western psychological reason with tradition.